Isolation of bacteria displaying potent antagonistic activity against fungi causes anthracnose disease in chili (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Tram TTN, Quang HT, Vu NQH, Nguyen PTT, Thi TNM, Phuong TTB, Thi PTD. 2023. Isolation of bacteria displaying potent antagonistic activity against fungi causes anthracnose disease in chili. Biodiversitas 24: 4919-4926. Anthracnose is a common disease on many crops caused by Colletotrichum species, and it leaves serious consequences, especially on chili. Beta-1,3 glucanase is a semi-constitutive hydrolytic enzyme that is involved in the biological regulation of plant pathogens. Its main function is the breakdown of ?-1,3-glucan, a major constituent of the fungal cell wall. In a study conducted in Vietnam's Quang Tri and Thua Thien Hue Provinces, researchers isolated five bacterial strains from soil where chili plants were grown. To induce the production of beta-1,3 glucanase, these isolates were cultivated in a nutrient-rich medium supplemented with 1% laminarin. The activity of beta-1,3-glucanase in the bacterial strains ranged from 0.31 to 1.72 U mL-1, and antagonistic activity against Colletotrichum spp. causes of anthracnose reached from 50.68 to 69.04%. Strain AT4 had strong antagonistic activity against C. scovillei HUCL1, C. siamensis PV6, and CL3 of 76.44, 62.65, and 68.04%, respectively. Molecular identification based on 16S-rRNA sequences showed that the strains were Paenibacillus polymyxa AT4, B. siamensis ML3, B. tequilensis ML4 and ML6, and B. velezensis GL7. AT4 and ML6 are potential strains for the control of anthracnose diseases caused by Colletotrichum spp. on chili peppers.
Keywords: β-1,3-glucanase, antagonistic bacteria, anthracnose, chili pepper, Vietnam